EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TAI (TEAM ASSISTED INDIVIDUALIZATION) BERBANTU MEDIA PEMBELAJARAN ADOBE FLASH 8.0 PADA MATERI POKOK SEGIEMPAT DITINJAU DARI MOTIVASI BELAJAR SISWA SMP NEGERI SE-KABUPATEN SUKOHARJO TAHUN PELAJARAN 2013/20 - Sari, Intan Novia; Mardiyana, Mardiyana; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aims of this research were to know: (1) which one of the learning model gave a better achievement between of the TAI assisted by adobe flash 8.0, TAI, and conventional; (2) which one of the students with students learning motivation categories had a better achievement between students with high, moderate or low learning motivation; (3) in each the students learning motivation categories, which one of the learning models gave a better achievement in mathematics between TAI assisted by adobe flash 8.0, TAI, or conventional; (4) in each the learning models, which one of the students learning motivation had a better achievement in mathematics between the students with high, moderate, or low students learning motivation.The type of the research was a quasi experimental research method. The population of the research was the seventh class students of State Junior Secondary School at Sukoharjo regency in Academic Year 2013/2014. They were taken by using the stratified cluster random sampling technique. The instruments used to gather the data of the research were test of learning achievement in Mathematics and questionnaire of the students learning motivation. The data analysis technique used was unbalanced two ways analysis of variance. Based on the data analysis, it was concluded as follows. 1) TAI assisted by adobe flash 8.0 results in a better learning achievement in Mathematics than TAI and conventional, the TAI model results in a better learning achievement in Mathematics than conventional. 2) The students with the high learning motivation had the same achievement as the students with moderate learning motivation, the students with the moderate learning motivation had the same achievement as the students with low learning motivation and the students with the high learning motivation had a better learning achievement in Mathematics than the students with low learning motivation. 3) In each students learning motivation, the TAI assisted by adobe flash 8.0 results in a better learning achievement in Mathematics than TAI and conventional, the TAI model results in a better learning achievement in Mathematics than conventional. 4) In each learning model, the students with the high learning motivation had the same achievement as the students with moderate learning motivation, the students with the moderate learning motivation had the same achievement as the students with low learning motivation and the students with the high learning motivation had a better learning achievement in Mathematics than the students with low learning motivation.Keywords: Team Assisted Individualization model, Adobe Flash 8.0, and students learning motivation.